1987
DOI: 10.1016/0035-9203(87)90001-0
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary ovalocytosis and reduced susceptibility to malaria in Papua New Guinea

Abstract: Ovalocytosis, an hereditary condition in which most erythrocytes are oval in shape, is a polymorphism that occurs in up to 20% or more of the population in Papua New Guinea and Malaysia. Due to the geographical correlation of the trait with endemic malaria, the possibility of a selective advantage in resistance to malaria has been raised. In a study of 202 individuals with greater than or equal to 50% oval red cells matched by age, sex and village of residence with controls having less than or equal to 30% ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…For example, the frequency of the deletion was 0.146 in a sample of healthy Papua New Guinea children whereas it was not present in any of the children with cerebral malaria (Genton et al, 1995 see also;Allen et al, 1999). Carriers also appear to be at lower risk of infection by both P. vivax and P. falciparum (Cattani et al, 1987; however, see Kimura et al, 2002).…”
Section: Slc4a1 or Band 3 Ovalocytosismentioning
confidence: 99%
“…For example, the frequency of the deletion was 0.146 in a sample of healthy Papua New Guinea children whereas it was not present in any of the children with cerebral malaria (Genton et al, 1995 see also;Allen et al, 1999). Carriers also appear to be at lower risk of infection by both P. vivax and P. falciparum (Cattani et al, 1987; however, see Kimura et al, 2002).…”
Section: Slc4a1 or Band 3 Ovalocytosismentioning
confidence: 99%
“…Ovalocytosis occurs at high frequencies (up to 20%) in the highly malarious lowlands of New Guinea but virtually disappears in the malaria-free highlands. Carriers of the trait are at reduced risk of infection with P. falciparum and, especially, P. vivax malaria (26).…”
Section: Ovalocytosismentioning
confidence: 99%
“…On the other hand, SAO individuals are fully susceptible to severe malaria anemia and clinical uncomplicated malaria. 18 Although early studies, conducted before the presence of the SAO trait could be determined unambiguously by polymerase chain reaction (PCR), suggested that SAO individuals exhibit some degree of protection against prevalence of malaria parasites or against high-density P falciparum infections, [20][21][22] later studies demonstrated that SAO individuals suffer high-density infections by P falciparum and this trait only has minor effects, if any, on the prevalence and density of P falciparum infections. 18,23 Our recent finding that SAO infected RBCs (IRBCs) have altered adherence properties compared with normal IRBCs (A.C., M. Mellombo, C.S.…”
Section: Introductionmentioning
confidence: 99%